Can role models influence female's decision to participate in the labor market? Evidence from a field experiment - Christina Martini; Viviana Urue\~na (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2021)
In this paper we experimentally test the effect of an intervention aimed at encouraging females to enter the labor market in Madagascar. We randomly assigned students in their last year of secondary education to watch a role model or a placebo video. In the role model videos, a female or a male narrate how they succeeded in achieving a goal they set for themselves. After video exposure, we gave female and male students the opportunity to apply for one of two types of jobs in our research team - assistant or coordinator. We find that the female role model encourages both females and males to apply for the advertised positions, compared to the placebo video. This positive treatment effect can partly be explained by participants' aspirations and current level of achievements. Moreover, we find that female students apply more often to the coordinator position compared to the control in the male role model treatment. Our results suggest that not only individuals from the in-group (females), but also males can serve as role models for females and foster behavioral changes.
Keywords: J16; C9; I25; N37; 330; Aspirations; Role models; Performance; Competition; Gender